1991
DOI: 10.3382/ps.0701936
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Sex, and Method of Rearing on Tibia Length and Mineral Deposition in Broilers

Abstract: Two experiments were conducted to determine linear growth and mineral deposition in the tibiae of Vantress x Arbor Acres broilers. In Experiment 1, birds were maintained in battery brooders for 21 days then housed in floor pens from Day 22 to 70. In the second experiment, birds were reared either in battery brooders and grow-out cages or floor pens from Day 1 to 63. Males and females were maintained separately. Birds in both trials were weighted at weekly intervals and three birds of each sex per treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 8 publications
3
24
1
2
Order By: Relevance
“…Rose et al (1996) confirmaram esta observação por não terem observado diferenças no peso, volume e comprimento ósseo até os 26 dias de idade, mas foram bastante evidentes aos 42 dias. O mesmo foi observado por Bond et al (1991), que não notaram diferenças no tamanho das tíbias em 7 semanas de idade, mas observaram diferentes nos animais adultos. Entretanto, para a AST e área da córtex óssea, Rose et al (1996) confirmaram o dimorfismo sexual desde o nascimento.…”
Section: Resultsunclassified
“…Rose et al (1996) confirmaram esta observação por não terem observado diferenças no peso, volume e comprimento ósseo até os 26 dias de idade, mas foram bastante evidentes aos 42 dias. O mesmo foi observado por Bond et al (1991), que não notaram diferenças no tamanho das tíbias em 7 semanas de idade, mas observaram diferentes nos animais adultos. Entretanto, para a AST e área da córtex óssea, Rose et al (1996) confirmaram o dimorfismo sexual desde o nascimento.…”
Section: Resultsunclassified
“…Studies have shown that the weight of the tibia of male chicks is higher than that of females (Bond et al, 1991;Yalcin et al, 2001).…”
Section: Bone Weightmentioning
confidence: 99%
“…Broiler and jungle fowl chicks exhibit similar ontogenetic patterns of organ growth. We have compared our measurements of jungle fowl organs (Jackson and Diamond 1995) with published measurements of broiler organs (Dror et al 1977;Pinchasov et al 1985;Bond et al 1991;Nitsan et al 1991b). In general, metabolically active organs that supply energy to the rest of the bird-the liver, pancreas, lungs, heart, crop, proventriculus, gizzard, and all regions of the small intestine-increase in relative mass in the first week or two after hatching, followed by relative decreases.…”
Section: Comparisons Between Broilers and Jungle Fowlmentioning
confidence: 99%
“…Except for these two surges in broilers, activities of both the glucose and the proline transporter, in all three intestinal regions, at most ages, are actually higher in jungle fowl than in broilers. Twoway ANOVAs for each nutrient, with strain and age as the main effects, showed that the strains differ overall in duo- Pinchasov et al (1985), and Bond et al (1991), jungle fowl data from Jackson and Diamond (1995). Straight lines are the lines of best fit from least-squares regression analyses.…”
Section: Intestinal Nutrient Uptakementioning
confidence: 99%
See 1 more Smart Citation